PLIOCENE-EARLY PLEISTOCENE ASTRONOMICALLY FORCED PLANKTONIC FORAMINIFERA ABUNDANCE FLUCTUATIONS AND CHRONOLOGY OF MEDITERRANEAN CALCAREOUS PLANKTON BIO-EVENTS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1993)
The absolute age estimates for calcareous plankton events proposed by the writer in a recent paper are discussed according to the new proposed paleomagnetic time scales. A re-interpretation of the sequence of lithological cycles recognized in the "Rossello composite section" makes their number perfectly comparable with the number of planktonic foraminifera abundance fluctuations in the same stratigraphic interval.An absolute age of 5.33 MA is estimated for the base of the Pliocene, as defined in the Capo Rossello section. Periodicity of the relative abundance fluctuations of the planktonic foraminiferal assemblages during the Early Pleistocene stratigraphic interval is estimated at about 41 kyr, well comparable with the periodicity of the obliquiry astronomical cycles. By correlation of the sequence of biostratigraphic events recorded in the Early Pleistocene interval in the Mediterranean sections with the sequence of abundance fluctuations, their absolute ages have been obtained, as well as the absolute age of chronostratigraphic boundaries. The base of the Pleistocene is at 1.83 MA and the top of the Early Pleistocene, coincident with the top of the Sicilian, is at 0.89 MA. A re-evaluation of the Oxygen isotopic Stages of the upper Singa section is proposed, on the base of paleomagnetic and calcareous plankton biostratigraphic data reported for this section. Correlation with the North Atlantic Site 607 proved that rhe G. oceanica s.l. FO, the C. macintyrei LO and rhe Gephyrocapsa sp.3 FO are slightly diachronous between the Mediterranean and the mid-North Atlantic high latitudes.
Keywords: Biochronology; Planktonic Foraminifera; Pliocene; Early Pleistocene; Mediterranean.